A new species group and two new species of freyine jumping spiders (Araneae, Salticidae, Aelurillini) - Rubio, Gonzalo Daniel; Nadal, María Florencia; Baigorria, Julián Emanuel Martín; Oklander, Luciana Inés; Edwards, G.B. (Museo Argentino de Ciencias Naturales "Bernardino Rivadavia", 2020)
Wedoquella apnnea sp. nov. and W. karadya sp. nov., two new species of the jumping spider subtribe Freyina are described and illustrated from specimens recently collected in Misiones and Chaco provinces, Northeastern Argentina. The new species are placed into a new group of Wedoquella because, although in body morphology they resemble the Phiale gratiosa group, the genital structures of both sexes more closely resemble those of Wedoquella, and a preliminary analysis based on mitochondrial COI sequences places this new group as sister to Wedoquella rather than to Phiale. Both new species are similar, but can be distinguished mainly by differences in the retrolateral tibial apophysis of the male palp. Females have a slight intraspecific color variation.